Diagnostic Utility of Bronchial Washing CBNAAT for Mycobacterium Tuberculosis in Sputum Smear Negative and Sputum CBNAAT Negative Patients of Suspected Pulmonary Tuberculosis - Shaik, Afshan Ali; Kakodkar, Uday; Borges, Cigy (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Diagnosis of sputum negative pulmonary tuberculosis can be challenging and time consuming, with many patients being put on empirical anti-tuberculosis treatment. Bronchoscopy helps in early diagnosis in such patients. Aims and Objectives: To assess the diagnostic utility of bronchial washing CBNAAT for Mycobacterium Tuberculosis in sputum smear negative and sputum CBNAAT negative patients of suspected pulmonary tuberculosis. Methodology: This case series was conducted on 71 patients in the Department of Pulmonary Medicine, Goa Medical College from May 2018- February 2020. Patients with suspected pulmonary tuberculosis on chest radiograph and/or CT thorax, but with sputum smear as well as CBNAAT for Mycobacterium Tuberculosis negative were subjected to flexible video bronchoscopy. Bronchial washings were collected from the affected lobes and the specimen were subjected to fluorescent microscopy, CBNAAT, MGIT, bacterial and fungal culture. Results: The diagnosis of tuberculosis was established in 23 (32.4%) patients in bronchial washings specimen by CBNAAT. These patients were followed up after 6 months of anti-tuberculosis treatment and have shown significant clinical and radiological improvement. Conclusion: Bronchoscopy is a useful tool in diagnosis of pulmonary tuberculosis in sputum negative patients. It also play an important role in diagnosis of other infectious /malignant disorder which can mimic tuberculosis.